Maternal folic acid supplementation with vitamin B12 deficiency during pregnancy and lactation affects the metabolic health of adult female offspring but is dependent on offspring diet. Issue 9 (17th April 2018) - Henderson, Amanda M.; Tai, Daven C.; Aleliunas, Rika E.; Aljaadi, Abeer M.; Glier, Melissa B.; Xu, Eric E.; Miller, Joshua W.; Verchere, C. Bruce; Green, Tim J.; Devlin, Angela M.
ABSTRACT: Epidemiologic studies have reported relationships between maternal high folate and/or low B12 status during pregnancy and greater adiposity and insulin resistance in children. The goal of this study was to determine the effects of maternal folic acid supplementation (10 mg/kg diet), with (50 mg/kg diet) and without B12, on adult female offspring adiposity and glucose homeostasis. Female C57BL/6J mice were fed 1 of 3 diets from weaning and throughout breeding, pregnancy, and lactation: control (2 mg/kg diet folic acid, 50 mg/kg diet B12 ), supplemental folic acid with no B12 (SFA‐B12 ), or supplemental folic acid with adequate B12 (SFA+B12 ). Female offspring were weaned onto the control diet or a Western diet (45% energy fat, 2 mg/kg diet folic acid, 50 mg/kg diet B12 ) for 35 wk. After weaning, control diet‐fed offspring with SFA—B12 dams had fasting hyperglycemia, glucose intolerance, lower p cell mass, and greater islet hepatocyte nuclear factor 1 homeobox a and nuclear receptor subfamily 1 group H member 3 mRNA than did offspring from control dams. In Western diet‐fed offspring, those with SFA—B12 dams had lower fasting blood glucose and plasma insulin concentrations, and were smaller than control offspring. Our findings suggest that maternal folic acid supplementation with B12 deficiency during pregnancy/lactation programs the metabolic health of adult female offspring but is dependent on offspring diet.—Henderson, A. M., Tai, D. C., Aleliunas, R. E., Aljaadi, A. M., Glier, M. B., Xu, E. E., Miller, J. W., Verchere, C. B., Green, T. J., Devlin, A. M. Maternal folic acid supplementation with vitamin B12 deficiency during pregnancy and lactation affects the metabolic health of adult female offspring but is dependent on offspring diet. FASEB J. 32, 5039–5050 (2018). www.fasebj.org